Ensuring the right to defense in the criminal process - Dinu Ostavciuc (Supremația Dreptului, 2022)
The right to defense is one of the essential principles of the criminal process. Violation of this right affects the fairness of the process and leads to procedural sanctions. In this article, the role of international and national legislation and practice will be analyzed regarding the application and observance of the principle of ensuring the right to defense, the role of the Constitutional Court and other legal institutions in this regard. Or, states are obliged to effectively guarantee the accused persons the right to defense, as this is a condition for the realization of the act of justice in a democratic state. Following the analysis carried out, we come with recommendations and explanations regarding the content of this principle, because it should not be seen as simple legal assistance, but has a more complex content.